(untitled) (Journal of Universal Science Research, 2025)
Listening comprehension is widely recognized as a core component of second and foreign language acquisition, as it underpins learners’ ability to develop effective communication skills. However, many language learners experience difficulties in understanding spoken input due to factors such as speed of speech, unfamiliar vocabulary, and limited exposure to authentic listening materials. This article examines the significance of listening comprehension in the EFL/ESL classroom and emphasizes the role of systematic instruction in its development. It presents a range of pedagogically grounded listening exercises organized into pre-listening, while-listening, and post-listening stages. These exercises are designed to enhance learners’ ability to identify main ideas, comprehend specific details, and interpret meaning in spoken texts. The article aims to provide language teachers with practical insights and classroom-oriented strategies for fostering effective listening comprehension and supporting overall language proficiency.